In vitro evaluation of electrospun gelatin‐bioactive glass hybrid scaffolds for bone regeneration. Issue 4 (15th May 2012) - Gao, Chunxia; Gao, Qiang; Li, Yadong; Rahaman, Mohamed N.; Teramoto, Akira; Abe, Koji
Abstract Organic–inorganic hybrid materials, composed of phases that interact on a nanoscale and a microstructure that mimics the extracellular matrix, can potentially provide attractive scaffolds for bone regeneration. In the present study, hybrid scaffolds of gelatin and bioactive glass (BG) with a fibrous microstructure were prepared by a combined sol–gel and electrospinning technique and evaluated in vitro. Structural and chemical analyses showed that the fibers consisted of gelatin and BG that were covalently linked by 3‐glycidoxypropyltrimethoxysilane to form a homogeneous phase. Immersion of the gelatin–BG hybrid scaffolds in a simulated body fluid (SBF) at 37°C resulted in the formation of a hydroxyapatite (HA)‐like material on the surface of the fibers within 12 h, showing the bioactivity of the scaffolds. After 5 days in SBF, the surface of the hybrid scaffolds was completely covered with an HA‐like layer. The gelatin–BG hybrid scaffolds had a tensile strength of 4.3 ± 1.2 MPa and an elongation to failure of 168 ± 14%, compared to values of 0.5 ± 0.2 MPa and 63 ± 2% for gelatin scaffolds with a similar microstructure. The hybrid scaffolds supported the proliferation of osteoblastic MC3T3‐E1 cells, alkaline phosphatase activity, and mineralization during in vitro culture, showing their biocompatibility. The results indicate that these gelatin–BG hybrid scaffolds prepared by a combination of sol–gel processing and electrospinning have potential for application in bone regeneration. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013